Initial-State Temperature of Light Meson Emission Source From Squared Momentum Transfer Spectra in High-Energy Collisions - Wang, Qi; Liu, Fu-Hu; Olimov, Khusniddin K. (Frontiers in Physics, 2021)
The squared momentum transfer spectra of light mesons, π0, π+, η, and ρ0, produced in high-energy virtual photon-proton (γ*p) → meson + nucleon process in electron-proton (ep) collisions measured by the CLAS Collaboration are analyzed by the Monte Carlo calculations, where the transfer undergoes from the incident γ* to emitted meson or equivalently from the target proton to emitted nucleon. In the calculations, the Erlang distribution from a multi-source thermal model is used to describe the transverse momentum spectra of emitted particles. Our results show that the average transverse momentum (⟨pT⟩) and the initial-state temperature (Ti) increase from lower squared photon virtuality (Q2) and Bjorken variable (xB) to higher one. This renders that the excitation degree of emission source, which is described by ⟨pT⟩ and Ti, increases with increasing of Q2 and xB.